The Muslim problematic: Muslims, state schools and security. Issue 2 (2nd April 2016) - Miah, Shamim
Abstract: Muslims are folk-devils that mark the ubiquitous moral panic. For some, the idea of the Muslim problematic signifies a long and worrying trend of creeping 'Islamification' of state schools. For others, the discourse of the Muslim problematic reflects the ongoing racial patholigisation of Britain's minoritised communities. One thing is for certain, the current debate marks a significant moment in the nature and function of the neoliberal state as it reframes race relation policy in Britain in the light of the security agenda. The Trojan Horse affair, surrounding claims of infiltration of radical Islam in state-run schools, marks a significant moment in the embedding of the security agenda in Britain's inner city schools through the medium of the Prevent agenda. It argues that one of the best ways of understanding the security agenda is by locating it within a broader sociological and historical context of the functioning of the racial state.